Mpox disease, diagnosis, and point of care platforms - Atceken, Nazente; Bayaki, Ikra; Can, Berk; Yigci, Defne; Tasoglu, Savas (WILEY, 2025)
Human Mpox disease (MPX) is an endemic zoonotic disease that develops when patients are infected with the Mpox virus (MPXV). MPXV shares a high level of genetic similarity to other poxviruses and the clinical presentation of MPX is similar to other poxvirus infections which can result in a delay in diagnosis. In addition, the MPXV virus is phylogenetically divided into two different clades which affects the severity of disease. In recent years, there has been an unusual worldwide spread of MPXV, leading to a global public health problem. The most important step in the fight against MPX is rapid, highly specific, and accurate diagnosis. Following the rapid spread of disease in recent years, efforts to develop diagnostic tests have gained momentum. Here, MPX, MPX epidemiology, and MPX diagnostic tests are discussed. Furthermore, biochemical diagnostic tests, molecular diagnostic tests and their development, and point-of-care (PoC) diagnostic applications are reviewed. Molecular diagnostic technologies such as polymerase chain reaction, recombinase polymerase amplification, and loop-mediated isothermal amplification methods that detect MPX are evaluated. Additionally, next-generation combined molecular techniques and their importance in PoC transition are explored.
Keywords: loop-mediated isothermal amplification (LAMP); Mpox (MPX); point-of-care (PoC) applications; polymerase chain reaction (PCR); recombinase polymerase amplification (RPA); MEDIATED ISOTHERMAL AMPLIFICATION; MONKEYPOX-VIRUS; POLYMERASE AMPLIFICATION; LAMP; INFECTION; DNA; OUTCOMES; ASSAYS; HUMANS; CLADES; Biotechnology & Applied Microbiology; Engineering; Pharmacology & Pharmacy